Efficacy of Sonoelastography Images in Solitary Cold Thyroid Nodule and Compared with Fine Needle Aspiration Cytology Findings (FNAC) - Ferdous, Jasmin; Rahman, Mahbub ur; Rahman, Hosne Ara; Hossain, Jamiul; Sharmin, Samira; Yasmin, Farida; Das, Jhorna; Hossain, Moazzem; Akther, Sharmin (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: To evaluate the validity of sonoelastography of cold thyroid nodule in diagnosis of malignant nodule with fine needle aspiration cytology analysis as the reference standard. Patients and Methods: This cross sectional study was conducted in the Institute of Nuclear Medicine & Allied Sciences (INMAS), Sir Salimullah Medical College (SMC) & Mitford Hospital campus, Dhaka, from July 2015 to June 2016 in 85 patients with solitary solid cold nodule. Eighty five nodules in these patients were examined by conventional ultrasound, ultrasound elastography and radionuclidescan. The final diagnosis was obtained from cytological findings. Tissue stiffness on ultrasound elastography was scored from 1 (low stiffness over the entire nodule) to 4 (high stiffness over the entire nodule). Results: The mean age was found 33.8±10.1 years with range from 12 to 58 years and male to female ratio was 1:5.1. The mean size of nodules was found 2.0±0.6 cm. Most (40.0%) of the patients were found in elastography score 2, 22(25.9%) score 1, 17(20.0%) score 4 and 12(14.1%) score 3. The validity of elastography scores had sensitivity 77.8%, specificity 86.2%, accuracy 83.5%, positive predictive values 72.4% and negative predictive values 89.3% for prediction of thyroid nodule. Conclusion: Considering the validity parameter the elastography may be effective diagnostic modality for evaluation of thyroid nodule. Bangladesh J. Nuclear Med. 19(2): 103-106, July 2016